“Woman in Priesthood” in Orthodox Judaism and Orthodox Christianity - Ю. Крайчева, Магдалена (Forum Theologicum Sardicense, 2025)
Magdalena Kraycheva, “Woman in Priesthood” in Orthodox Judaism and Orthodox Christianity. The article focuses on the issue of ‘woman and priesthood relations’ in contemporary Orthodox Judaism and Orthodox Christianity. Modern societal trends are moving towards gender equality. The feminist movement of the 20th century had a significant impact on Judaism, particularly within the liberal branches of Reform and Reconstructionist Judaism. In Christian Orthodoxy, while there is no feminist movement, there have been discussions over the past few decades about the role of women in the priesthood. The ‘secret of gender’ is a central topic in these debates, especially among Christians, due to the central dogma of the Incarnation. While gender equality is not a Christian concept, the idea of Love transcends the Law, in which distinctions between men and women are rooted.